Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L.; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination

Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination

Ex Vitro Acclimatization of Laelia halbingeriana Plants Grown in Different Media and Fertilization Doses - Heredia-Rendon, A; Enriquez-del Valle, J; Campos, G V; Marini, F; Velasco, V A; Damon, A (INTERNATIONAL SYMPOSIUM ON SOILLESS CULTURE AND HYDROPONICS, 2009)
In vitro plants of the orchid Laelia halbingeriana were obtained from seed germination. The plants were grown and established in different organic substrates mixes. The substrates resulted from the mix of compost and charcoal, land of mount and Holm oak bark, and peat and volcanic tuff. The plants were fertilized with four levels of nitrogen (0, 10, 30 and 50 mg L-1). Six months after the establishment, 64.84% to 80.22% of the plants were adapted to the climate conditions. The highest survival rates in plantlets were obtained in the adaptation conditions using peat-volcanic tuff and nitrogen doses of 30 and 50 mg L-1. These plants had an average of 8.01 cm height, 5.15 leafs, 2.66 pseudo-bulbs, 77 to 89 mg of total accumulated dry matter, and 42 to 45% of C in leaves and pseudo-bulbs. The fertilization had a significant effect (P <= 0.05) on the plants growth and a highly significant effect (P <= 0.01) on number of leaves, width of the major leaf and the number of pseudo-bulbs; The interaction substrates and fertilization had a highly significant effect (P <= 0.01) on the nitrogen content in leaves and pseudo-bulbs.
Keywords: development; in vitro; nitrogen; Orchidacea; Seeds

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - GARCÍA-MARTÍN, G (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - Garcia-Martin, G. (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Shoot development in Quercus suber L. somatic embryos - Gonzalez-Benito, M Elena; García-Martín, Gemma; Antonio Manzanera, José (In Vitro Cellular & Developmental Biology - Plant, 2002)
N 6 -Benzyladenine (BA; 0.04–4 mM) application to germinated Quercus suber somatic embryos considerably increased caulinar apex elongation frequency and maintained active growth in the plantlets, although it did not have a signiﬁcant effect on the percentage of shoots with normal morphology. The addition of 0.5 mM indoleacetic acid together with the cytokinin did not have any effect. The use of a low concentration (0.04mM) of BA allowed the appropriate radicle elongation in all germinating somatic embryos, but higher concentrations arrested this elongation.
Keywords: Cork oak; growth regulators; in vitro; plantlet.

Composition and metabolizable energy of feed used by fallow deer (Dama dama) in a coastal Mediterranean ecosystem - Poli, B M; Focardi, S; Tinelli, A (Small Ruminant Research, 1996)
Data on the impact of a population of about 1000 (spring estimate) fallow deer (Dama &ma) on eight shrubs and mono- and dicotyledonous plants were collecred in a coastal Mediterranean environment from December 1990 to March 1992. Four species of shrubs (Cistus salvifoiius, Phillyrea larifolia, Rubus ulmifolius. Quercus ibex) and mixed graminoids were preferentially consumed. In autumn-winter the acorns of several species, Q. cerris and Q. ilex in particular, were also consumed. We determined the chemical composition, in vivo digestibility coefficients and metabolizable energy content of the feed. On average, R. ulmifolius had the lowest fibre content (18% DM) and the highest protein content (12% DM), organic matter digestibility (59%) and metabolizable energy value (2083 kcal ME kg- ’ DM). C. saluifolius, P. fafifolia and mixed graminoids did not differ significantly in organic matter digestibility (OMD) and nutritive value (I 801, 1765 and 1557 kcal ME kg-’ DM, respectively), while Q. ilex had the lowest nutrient estimates with 32% OMD and 1362 kcal ME kg-’ DM. Forage quality traits usually peaked in spring and autumn. Metabolizable energy was positively correlated with protein, neutral detergent fibre and N-free extractives contents, and negatively correlated with the acid detergent fibre content. Acorns were generally highly digestible; in particular, the seed of Q. farniu and Q. ilex showed 80% and 83% OMD, respectively. In a Mediterranean environment the summer seems the most critical season for fallow deer. The results of this work are important for assessing the carrying capacity of wild Mediterranean ecosystems for fallow deer.
Keywords: digestibility; Fallow deer; Feed quality; in vitro; Mediterranean ecosystems